(untitled) (Journal of Nepalese Business Studies, 2023)
In this strategic human resource management era, employees are the most crucial components in the business world. Employers must consider how their workforce views the company and its brand. The study aims to explore employees’ perception of employer branding in the Nepalese Insurance Industry. The study also examines the influence of employers’ brands on employees’ perceptions in the Nepalese industry sectors. The research obtained information from the 400 employees working in the insurance industry by using convenience sampling techniques. However, 44 were incomplete information, 31 were removed for validity, and 325 were applicable for analysis. The structured questionnaire was prepared based on a five-point Likert scale from strongly disagree to strongly agree to evaluate employees’ perceptions. SPSS 20.0 software was used to assist in data analysis. Information was analyzed by descriptive analysis methods in which frequency analysis, cross tab, mean, and standard deviation were considered. The study’s findings explained employees’ favorable perceptions toward insurance companies’ brands. The employer’s branding highly impacted employees’ perceptions. Employees had a favorable opinion of their organization when their overall employer branding score was high. Employees with higher education levels had a positive opinion of employer brands, but people with lower education levels had a negative perception. The majority of employees agree with the company brand. Therefore, there is a greater need for insurance companies to create strategies necessary to guarantee that their employees will stay in the same workplace in the future. Employer branding benefits an organization’s recruiting efforts and lowers recruitment expenditures. Additionally, the research explains employers’ brands helpful for staff retention and lower employee turnover rates. So, the employer brand may be used to categorize the necessary strategies.